Effectiveness of the Textbooks on Structure and Function of Cells in Reproductive System Material - Ruqiah Ganda Putri Panjaitan; Titin Titin; Yohanes Gatot Sutapa Yuliana (JETL (Journal of Education, Teaching and Learning), 2019)
A well-conducted learning activity is supported by the availability of teaching materials, among many other supportive aspects. One of the most common teaching materials is textbook. This study aims to find out the effectiveness of the textbook on the structure and function of cells in reproductive system material for eleventh-grade students in high school. This study applied a descriptive method, and the data analysis used the Gregory test involving two validators. Three aspects that had been validated are presentation, content, and language consisting of fifteen criteria. The result of validation showed the validity construct for the aspect of the presentation is 1, the aspect of content is 1, and the aspect of language is 1, so the criteria for each aspect are very high. It concluded that the textbook can be used as a teaching material for the structure and function of cells in reproductive system material.